In vitro extraction and fermentation of polyphenols from grape seeds (Vitis vinifera) by human intestinal microbiota. Issue 4 (16th March 2016) - Zhou, Li; Wang, Wei; Huang, Jun; Ding, Yu; Pan, Zhouqiang; Zhao, Ya; Zhang, Renkang; Hu, Bing; Zeng, Xiaoxiong
Abstract : The effects of several parameters on the extraction yield of total polyphenols from grape seeds by pressurized liquid extraction were investigated. Abstract : The effects of several parameters on the extraction yield of total polyphenols from grape seeds by pressurized liquid extraction were investigated. The highest recovery of total polyphenols occurred at 80 °C within 5 min, and a single extraction allowed a recovery of more than 97% of total polyphenols. Following the purification with macroporous resin, the effects of grape polyphenols (>94.8%) on human intestinal microbiota were monitored over 36 h incubation by fluorescence in situ hybridization, and short-chain fatty acids (SCFAs) were measured by HPLC. The result showed that the grape polyphenols promoted the changes in the relevant microbial populations and shifted the profiles of SCFAs. Fermentation of grape polyphenols resulted in a significant increase in the numbers of Bifidobacterium spp. and Lactobacillus – Enterococcus group and inhibition in the growth of the Clostridium histolyticum group and the Bacteroides – Prevotella group, with no significant effect on the population of total bacteria. The findings suggest that grape polyphenols have potential prebiotic effects on modulating the gut microbiota composition and generating SCFAs that contribute to the improvements of host health.